A Polyamide Single‐Ion Electrolyte Membrane for Application in Lithium‐Ion Batteries. Issue 8 (23rd July 2014) - Sun, Yubao; Rohan, Rupesh; Cai, Weiwei; Wan, Xifei; Pareek, Kapil; Lin, An; Yunfeng, Zhang; Cheng, Hansong
Abstract A bis(sulfonyl)imide incorporated, high‐molecular‐weight gel single‐ion polyamide polymer electrolyte (LiPA) is designed and synthesized by using a polycondensation reaction followed by exchange of H+ with Li+ ions. All the bis(sulfonyl)imide anions are immobilized in the polymer chains, which gives rise to a substantially higher lithium cation transference number of 0.88 than the corresponding values of conventional liquid‐based electrolytes or dual‐ion gel polymer electrolytes of inorganic salts, and also provides smooth channels for Li+ ion transport in the polymer matrix. A gel single‐ion polymer electrolyte membrane, comprised of polyvinylidene fluoride (PVDF) and LiPA, is successfully prepared with an ionic conductivity of 3.8×10−4 S cm−1 at room temperature, well suited for applications in lithium‐ion batteries. Good battery performance of the membrane is demonstrated in an assembled Li‐ion battery cell at both room temperature and at elevated temperature.